2019
DOI: 10.1590/0001-3765201920180452
|View full text |Cite
|
Sign up to set email alerts
|

A low-protein, high carbohydrate diet induces increase in serum adiponectin and preserves glucose homeostasis in rats

Abstract: How to cite: CeOlIN P eT Al. 2019. A low-protein, high carbohydrate diet induces increase in serum adiponectin and preserves glucose homeostasis in rats. An Acad Bras Cienc 91: e20180452.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Yagi et al found that a low-protein diet significantly elevated serum adiponectin level and also increased the amount of adiponectin secreted by adipocytes isolated from white adipose tissue ( 41 ). Also, Ceolin et al in an animal model study showed that serum adiponectin level was higher in animals fed with a low protein diet than standard protein diet ( 42 ). The results of a study on older women participating in a resistance-based exercise program showed that women with a high protein diet had significantly higher adiponectin content compared to those with a high carbohydrate diet ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yagi et al found that a low-protein diet significantly elevated serum adiponectin level and also increased the amount of adiponectin secreted by adipocytes isolated from white adipose tissue ( 41 ). Also, Ceolin et al in an animal model study showed that serum adiponectin level was higher in animals fed with a low protein diet than standard protein diet ( 42 ). The results of a study on older women participating in a resistance-based exercise program showed that women with a high protein diet had significantly higher adiponectin content compared to those with a high carbohydrate diet ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The weight loss observed in HCD in respect to the ND group may be partially explained by the lower food consumption (constituted by 13.2% protein) observed in this study. This dietary deficiency can decrease muscle mass by increasing thermogenesis in adipose tissue [ 31 ], and induce an increased insulin resistance which is known to reduce muscle protein synthesis [ 32 ]. Our findings agree with previous studies where no weight gain has been observed after HCD [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased maternal food intake after PR during gestation has been well documented and has emerged as a mechanism to compensate for the lack of amino acid supply [ 33 , 34 , 35 , 36 ]. We showed that food intake was drastically decreased during the second half of lactation, which could deeply alter breast milk quality and body composition, given the high energy requirements for nursing [ 37 ].…”
Section: Discussionmentioning
confidence: 99%